Visual search for animal fear-relevant stimuli in children - Waters, A.; Lipp, Ottmar; Spence, S. (John Wiley & Sons Ltd., 2008)
This study examined visual search for animal fear stimuli and whether high fear levels influence children's visual search. Experiment 1 was conducted with adults to provide a control for the effects observed in Experiments 2 and 3 with children. Both adults and children were faster to locate snakes and spiders among flowers and mushrooms than vice versa in arrays of nine but not of four pictures. Both groups were also faster to determine target absence from arrays of snakes and spiders than flowers and mushrooms regardless of array size. Experiment 3 showed that compared with low-fearful children, those who feared snakes and spiders did not show a search advantage for determining target absence from arrays containing snakes and spiders compared with flowers and mushrooms. These results support preferential search for animal fear stimuli in children and suggest that high fearfulness affects children's ability to disengage attention from feared stimuli. © The Australian Psychological Society Ltd.